A critical thinking challenge for the chief of staff: a case study. (1st January 2012) - Long, Kenneth; Morrison, Eric; Lawler, M.
A military college for organisational-level leaders identified the improvement of the critical thinking (CT) curriculum as a high priority. The first cycle of design, development and implementation was not successful due to a lack of time and assembling a team that did not have representation from all teaching departments, curriculum developers, and operations staff. After conducting a detailed after action review and an appreciative sharing of knowledge (ASK) project to understand what had happened, the college's chief of staff had to develop a strategy to plan for a second cycle of design to develop a critical thinking course that could be successfully integrated into the year-long academic programme of each teaching department within the college. The chief of staff was faced with a complex social and technical challenge with many different stakeholders. This case study examines those challenges.